A placebo-controlled clinical trial to evaluate the effectiveness of massaging on infantile colic using a random-effects joint model - Mansouri S; Kazemi I; Baghestani AR; Zayeri F; Nahidi F; Gazerani N (Dove Medical Press, 2018)
Samaneh Mansouri,1 Iraj Kazemi,2 Ahmad Reza Baghestani,3 Farid Zayeri,1 Fatemeh Nahidi,4 Nafiseh Gazerani4 1Department of Biostatistics, Faculty of Paramedical Sciences, Shahid Beheshti University of Medical Sciences, Tehran, Iran; 2Department of Statistics, Faculty of Sciences, University of Isfahan, Isfahan, Iran; 3Department of Biostatistics, Faculty of Paramedical Sciences, Physiotherapy Research Center, Shahid Beheshti University of Medical Sciences, Tehran, Iran; 4Department of Midwifery and Reproductive Health, Shahid Beheshti University of Medical Sciences, Tehran, Iran Background: Infantile colic viewed as a non-dangerous prevalent issue could lead to stress in parents and long-term negative consequences in ex-colicky children. Researchers have not been successful in finding a certain treatment for colic symptoms. Studies suggest completely different approaches as its treatment. Massage therapy as an alternative method in reducing colic symptoms has been recommended in several studies.Methods: A total of 100 colicky infants in a single blind study were randomly specified to two equal groups of intervention and control. Infants in the intervention group received massage for 15–20 minutes once during the day and once at night before sleep, while infants in the control group were rocked for 15–25 minutes when the symptoms of colic appeared. Parents recorded the details of the colic symptoms in a diary every day. All these outcomes were modeled simultaneously via a random-effects joint model.Results: Among 100 infants included in the analysis, 48% were female; 91% of all infants were breastfed and 54% of them were born via normal vaginal delivery. In general, the effect of massage therapy on colic symptoms was assessed using the joint model. Our findings illustrated that massaging colicky infants would substantially reduce colic symptoms and increase the sleep duration in babies compared with the rocking group (P<0.001).Conclusion: Massage therapy could be considered as an effective method in reducing colic symptoms. Mean of the symptoms dropped significantly in the intervention group compared with that in the rocking group. Our study also represents that a relevant and correct statistical model could result in more reliable findings. Keywords: infantile colic, massage therapy, clinical trial, random-effects joint model